Interventional Planning for Endovascular Revision of a Lateral Tunnel Fontan: A Patient-Specific Computational Analysis - Ahmed, Yunus; Tossas-Betancourt, Christopher; van Bakel, Pieter A. J.; Primeaux, Jonathan M.; Weadock, William J.; Lu, Jimmy C.; Zampi, Jeffrey D.; Salavitabar, Arash; Figueroa, C. Alberto (Frontiers in Physiology, 2021)
Introduction. A 2-year-old female with hypoplastic left heart syndrome-variant, a complex congenital heart defect (CHD) characterized by the underdevelopment of the left ventricle, presented with complications following single ventricle palliation. Diagnostic work-up revealed elevated Fontan pathway pressures, as well as significant dilation of the inferior Fontan pathway with inefficient swirling flow and hepatic venous reflux. Due to the frail condition of the patient, the clinical team considered an endovascular revision of the Fontan pathway. In this work, we performed a computational fluid dynamics (CFD) analysis informed by data on anatomy, flow, and pressure to investigate the hemodynamic effect of the endovascular Fontan revision. Methods. A patient-specific anatomical model of the Fontan pathway was constructed from magnetic resonance imaging data using the cardiovascular modeling software CRIMSON. We first created and calibrated a pre-intervention 3D-0D multi-scale model of the patient’s circulation using fluid-structure interaction analyses and custom lumped parameter models, including the Fontan pathway, the single ventricle, arterial and venous systemic, and pulmonary circulations. Model parameters were iteratively tuned until simulation results matched clinical data on flow and pressure. Following calibration of the pre-intervention model, a custom bifurcated endograft was introduced into the anatomical model to virtually assess post-intervention hemodynamics. Results. The pre-intervention model successfully reproduced the clinical hemodynamic data on regional flow splits, pressures, and hepatic venous reflux. The proposed endovascular repair model revealed increases of mean and pulse pressure at the IVC of 6% and 29%, respectively. Inflows at the SVC and IVC were each reduced by 5%, whereas outflows at the LPA and RPA increased by 4%. Hepatic venous reflux increased by 6%. Conclusions. Our computational analysis indicated that the proposed endovascular revision would lead to unfavorable hemodynamic conditions. For these reasons, the clinical team decided to forgo the proposed endovascular repair and to reassess the management of this patient. This study confirms the relevance of CFD modeling as a beneficial tool in surgical planning for single ventricle CHD patients.